A phosphatidic acid-binding lncRNA SNHG9 facilitates LATS1 liquid–liquid phase separation to promote oncogenic YAP signaling - Li, Rui-Hua; Tian, Tian; Ge, Qi-Wei; He, Xin-Yu; Shi, Cheng-Yu; Li, Jun-Hong; Zhang, Zhen; Liu, Fang-Zhou; Sang, Ling-Jie; Yang, Zuo-Zhen; Liu, Ya-Zhuo; Xiong, Yan; et al. (Cell research, 2021)
Long noncoding RNAs (lncRNAs) are emerging as a new class of important regulators of signal transduction in tissue homeostasis and cancer development. Liquid–liquid phase separation (LLPS) occurs in a wide range of biological processes, while its role in signal transduction remains largely undeciphered. In this study, we uncovered a lipid-associated lncRNA, small nucleolar RNA host gene 9 ( SNHG9 ) as a tumor-promoting lncRNA driving liquid droplet formation of Large Tumor Suppressor Kinase 1 (LATS1) and inhibiting the Hippo pathway. Mechanistically, SNHG9 and its associated phosphatidic acids (PA) interact with the C-terminal domain of LATS1, promoting LATS1 phase separation and inhibiting LATS1-mediated YAP phosphorylation. Loss of SNHG9 suppresses xenograft breast tumor growth. Clinically, expression of SNHG9 positively correlates with YAP activity and breast cancer progression. Taken together, our results uncover a novel regulatory role of a tumor-promoting lncRNA (i.e., SNHG9 ) in signal transduction and cancer development by facilitating the LLPS of a signaling kinase (i.e., LATS1).